Retrieving Molecular Structural Information and Tracking HNC/HCN Isomerization Process with High Harmonic Generation by Ultrashort Laser Pulses - Ty, Nguyen Ngoc; Hoang, Le Van; Tuoc, Vu Ngoc; Thu, Le Anh (Communications in Physics, 2012)
We investigate the possibility of applying the iterative method, suggested in our previous work, for HCN molecule and its HNC isomer. We found that the high-order harmonic generation (HHG) spectra are quite insensitive to the change of H-C (or H-N) bond length so that only the inter-nuclear C-N distance can be retrieved from the high-order harmonic spectra using ultrashort intense lasers. Furthermore, by analyzing the HHG spectra emitted by HCN during the chemical reaction path of isomerization we identify the intensity peaks nearby the stable, meta-stable and transition states. This finding can be useful for tracking the HNC/HCN isomerization process